Research of intelligent reasoning system of Arabidopsis thaliana phenotype based on automated multi-task machine learning - Yuan, Peisen; Xu, Shuning; Zhai, Zhaoyu; Xu, Huanliang (Frontiers in Plant Science, 2023)
Traditional machine learning in plant phenotyping research requires the assistance of professional data scientists and domain experts to adjust the structure and hyperparameters tuning of neural network models with much human intervention, making the model training and deployment ineffective.